Brome Hay Cost-Return Budget in Central and Eastern Kansas - Dumler, Troy J.; Shoup, Douglas; O'Brien, Daniel M.; Duncan, Stewart R. (My University, 2015)
This publication compares the income per acre and cost per acre of producing brome hay in central and eastern Kansas.
MF2146_2015_04
Keywords: MF2143; Crops; Economics; MF